Integrating Independent Curriculum with Social Context: Contextual Teaching and Learning (CTL) as an Effective Learning Model in Early Elementary School Grades - Alfia Usmi Latifah; Keyla Zahra; Nazwa Putri Rizkita; Tin Rustini (Penerbit Hellow Pustaka, 2024)
Education is a lifelong learning process that is inseparable from human life, so teachers must provide appropriate guidance and teaching so that learning becomes meaningful. Social studies learning contains various fields of study that study scientific disciplines with the aim of developing abilities and quality of life so that students are able to be sensitive to social problems around them. The independent curriculum helps social studies learning become more adaptive and supports the Contextual Teaching and Learning (CTL) learning model to strengthen the link between learning material and students' real-life context. Through a descriptive-qualitative literature study approach, it was concluded that integration of the independent curriculum with social context through the Contextual Teaching and Learning (CTL) approach with the Teams Game Tournament (TGT) learning strategy in early elementary grades can help increase the relevance of the material to students' real lives